1996
DOI: 10.1074/jbc.271.50.31775
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Functional Interaction of Rabphilin-3A with α-Actinin

Abstract: Rabphilin-3A is a downstream target molecule of Rab3A small GTP-binding protein and implicated in Ca 2؉dependent neurotransmitter release. Here we have isolated a rabphilin-3A-interacting molecule from a human brain cDNA library by the yeast two-hybrid method and identified it to be ␣-actinin, known to cross-link actin filaments into a bundle. ␣-Actinin interacts with the N-terminal region of rabphilin-3A, with which GTPRab3A interacts, and this interaction stimulates the activity of ␣-actinin to cross-link ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 46 publications
2
81
0
Order By: Relevance
“…From this point of view, there may be a good relationship between the Rho-and Rac-regulated reorganization of actin filaments and Ca 2þ -dependent exocytosis, but the exact relationship between them has not been clarified. We have recently found that the Rab3A-rabphilin-3A system, which is involved in Ca 2þ -dependent exocytosis, modulates the activity of a-actinin to cross-link actin filaments into a bundle (Kato et al 1996). These results, together with the present results, suggest that the Rho and Rab family member-regulated reorganizations of actin filaments are cooperatively involved in Ca 2þ -dependent exocytosis.…”
Section: Figuresupporting
confidence: 84%
“…From this point of view, there may be a good relationship between the Rho-and Rac-regulated reorganization of actin filaments and Ca 2þ -dependent exocytosis, but the exact relationship between them has not been clarified. We have recently found that the Rab3A-rabphilin-3A system, which is involved in Ca 2þ -dependent exocytosis, modulates the activity of a-actinin to cross-link actin filaments into a bundle (Kato et al 1996). These results, together with the present results, suggest that the Rho and Rab family member-regulated reorganizations of actin filaments are cooperatively involved in Ca 2þ -dependent exocytosis.…”
Section: Figuresupporting
confidence: 84%
“…24 As far as rabphilin-3A, it has been shown that binding to ␣-actinin is able to increase the actin bundling activity of ␣-actinin. 9 Because the binding is inhibited by the GTP-bound form of Rab3A, the authors have hypothesized that, through switching the GTPase on and off and alternatively binding of rabphilin to Rab3A and ␣-actinin, these molecules behave like a timer that prepares vesicles for docking/fusion events by cytoskeletal reorganization. Further studies are needed to understand whether these processes are operative also in podocytes and whether they account for at least some of the cytoskeletal remodeling observed in normal glomeruli and altered in disease.…”
Section: Discussionmentioning
confidence: 99%
“…In absence of Rab3A, rabphilin-3A can bind to the cytoskeletal protein ␣-actinin increasing its actin filament bundling activity. 9 The carboxy (COOH) terminus of rabphilin-3A contains two C2 (protein kinase C-homology-2) domains (C2A and C2B) that bind to calcium and phospholipids and are homologous to the C2 domains of synaptotagmin. 10 In addition, the C2 domains can bind to another cytoskeletal protein, ␤-adducin, an actin-binding molecule that acts in the assembly of spectrin-actin complexes at the plasma membrane.…”
mentioning
confidence: 99%
“…Elevation in intracellular Ca 2+ levels induces vesicle docking and fusion events at the plasma membrane mediated by SNARE proteins. In addition to these fusion events, several other factors involved at different stages of the secretory pathway are reported to be potential Ca 2+ targets during the regulation of neurotransmitter release, e.g., protein kinases [49] as well as other Ca 2+ -regulated proteins like rabphilin, α-actinin [50] and β-adductin [51], which are involved in the regulation of actin filament organization. Here, we show that in the meshwork of actin filaments, a pool of MIA protein-containing secretory vesicles is stored and is only visible in adherent, non-migrating melanoma cells.…”
Section: Mia Protein Secretion Is a Ca 2+ -Regulated Process And Is Dmentioning
confidence: 99%